Crowdsourcing 2019
DOI: 10.4018/978-1-5225-8362-2.ch022
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Survey Research Using MTurk

Abstract: This chapter presents an introduction to crowdsourcing for survey participant recruitment. It also discusses best practices and ethical considerations for conducting survey research using Amazon Mechanical Turk (MTurk). Readers will learn the benefits, limitations, and trade-offs of using MTurk as compared to other recruitment services, including SurveyMonkey and Qualtrics. A synthesis of survey design guidelines along with a sample survey are presented to help researchers collect the best quality data. Techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…For example, Amazon's Mechanical Turk (MTurk), an online crowdsourcing website, can provide quick, easy, and inexpensive access to online research participants; however, there are concerns surrounding the quality and integrity of responses ( Dennis et al, 2020 ; Goodman et al, 2013 ). While such platforms can be a useful source of convenience samples, researchers are encouraged to be mindful of the limitations and employ more stringent measures to provide highly transparent and reproducible science ( Chambers and Nimon, 2019 ). The pandemic has also highlighted disparities between countries.…”
Section: Rolling With the Punches: Going Online Amidst The Pandemicmentioning
confidence: 99%
“…For example, Amazon's Mechanical Turk (MTurk), an online crowdsourcing website, can provide quick, easy, and inexpensive access to online research participants; however, there are concerns surrounding the quality and integrity of responses ( Dennis et al, 2020 ; Goodman et al, 2013 ). While such platforms can be a useful source of convenience samples, researchers are encouraged to be mindful of the limitations and employ more stringent measures to provide highly transparent and reproducible science ( Chambers and Nimon, 2019 ). The pandemic has also highlighted disparities between countries.…”
Section: Rolling With the Punches: Going Online Amidst The Pandemicmentioning
confidence: 99%
“…Participants can be screened for specific characteristics such as US residency. Although Mturk has both strengths and limitations like any source of data (14) , several empirical studies have indicated that samples recruited in this manner match the demographics of the USA more closely than typical convenience or Internet samples and yield high-quality data (15)(16)(17) . Mturk has been used successfully to conduct research on eating habits in general and food parenting practices specifically (18,19) .…”
Section: Data Collection Proceduresmentioning
confidence: 99%